2002
DOI: 10.1001/archneur.59.8.1249
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Worsening of Spatial and Chromatic Processing Deficits in Parkinson Disease

Abstract: Impairments of CD and CS in PD are progressive over time. Visual deficits may influence overall motor function and lead to enhanced motor impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 10 publications
4
84
0
1
Order By: Relevance
“…Sensory deficits have been documented in PD, particularly in the olfactory and visual domains [5][6][7][21][22]. Visual deficits in PD are subtle and not likely to be discovered during routine neurological examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory deficits have been documented in PD, particularly in the olfactory and visual domains [5][6][7][21][22]. Visual deficits in PD are subtle and not likely to be discovered during routine neurological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PD were reported to have reduced visual acuity [5], color vision [6], and contrast sensitivity [7]. It has also been reported that there is an increased visual dependence perceptually in patients with PD [8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most typical features of PD is reduced contrast sensitivity (CS), which is also assessed by psychophysiological methods [4,5]. In this respect, Hamilton test, Pelli-Robsons charts and software options such as Zebra 3 showing different chromatic and achromatic sinusoidal grids of different spatial frequency.…”
Section: IIImentioning
confidence: 99%
“…Later studies showed that defects in the visual system contribute greatly to motor disorders in PD, such as freezing, walking disturbance, postural disorder and falls, and can also, among other factors, induce visual hallucination [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Color vision abnormalities are among the non-motor clinical characteristics of PD (Prise et al, 1992;Büttner et al, 1995), and impairments in color discrimination and contrast sensitivity in PD are progressive over time (Diederich et al, 2002). The severity of the axial www.intechopen.com motor symptoms has been shown to be more closely related to visual dysfunction than mental function.…”
Section: Color Discriminationmentioning
confidence: 99%